PERLINDUNGAN HUKUM NASABAH OLEH BANK SEBAGAI UPAYA PENINGKATAN KEPERCAYAAN MASYARAKAT PENYIMPAN DANA - Aniek Tyaswati WL (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Efforts to increase the Bank's role as a collector and distributor of public funds needs to be done by taking into account the safety factor for the public funds entrusted to the bank because the bank's activities in the deployment of public funds depends on public confidence to put their funds. This confidence can be obtained in the presence of legal certainty in regulation and bank supervision and deposit insurance upon bank customers, through supervision and guidance to banks in Indonesia which is done by Bank Indonesia. Examination of the implementation of banking activities is basically an attempt by Bank Indonesia in order to control the banking activities in order to operate in accordance with applicable laws and regulations, the existence of Deposit Guarantee institutions and an opportunity for the depositors community in the completion action of customer complaints is a form of legal protection against bank customers or the public depositors.